A-183 A Preliminary Study of Comfort with Computers and Analog Tasks in Relation to Older Adults' Performance in Virtual Reality. (28th August 2020) - L, Williams; A, Coldiron; A, Sandlin; E, Flores; J, Flair; D, Lee; N, Tran; M, Barnett
Abstract: Objective: Neuropsychologists are using virtual reality to simulate everyday activities in order to increase ecological validity in neuropsychological assessments (Kane & Parsons, 2017). However, relatively little is known about the extent to which comfort with computers and analog tasks influences older adults' performance on virtual reality-based tasks. Methods: Healthy older adults (N = 42) rated how comfortable they are with computers and cooking meals in daily life and completed the Virtual Kitchen Protocol, a measure of procedural learning and memory for meal preparation tasks. Results: Both higher comfort with cooking meals in a real kitchen and higher comfort with computers were associated with better learning, immediate recall, and delayed recall of the procedural task in virtual reality. However, comfort with computers did not explain a significant amount of variance in performance beyond comfort cooking in a real kitchen. Conclusion: While both comfort with computers and analog versions of tasks may relate to older adults' learning and memory in virtual reality, performance may be primarily related to analog abilities.